The status quo of systematic reviews published in high-impact journals in Korea: a study focused on protocol registration and GRADE use - Mi Ah Han; Seong Jung Kim; Eu Chang Hwang; Jae Hung Jung (Epidemiology and Health, 2022)
OBJECTIVES This study investigated the status quo of systematic reviews published in major journals in Korea from the perspective of protocol registration and adopting the grading of recommendation, assessment, development and evaluation (GRADE) system. METHODS We examined systematic reviews published in Korea’s top 15 medical journals from 2018 to 2021. Teams of 2 reviewers assessed the studies’ eligibility criteria and extracted data independently and in duplicate. We collected information on study characteristics, protocol registration, and GRADE use of the included reviews, and reviewed the “Instructions for Authors” of the selected journals to assess any guidance related to systematic reviews. RESULTS Out of the 126 identified reviews, 18 (14.3%) reported that they registered or published their protocol. Only 5 (4.0%) rated the certainty of evidence; and all 5 used the GRADE system. Only 6 of 15 journals mentioned systematic reviews in their “Instructions for Authors.” Six journals endorsed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework for systematic review reporting (2 mandatory, 3 recommended, and 1 unclear). None of the journals included mentioned protocol registration or certainty of evidence in their authors’ guidelines. CONCLUSIONS Overall, the proportion of systematic reviews that had prior protocol registration or used the GRADE approach to rate the certainty of evidence was very low. Our study highlights the need for adherence to systematic review standards in medical journals in Korea, including prior protocol registration and certainty of evidence assessment. Our review will help improve the quality of systematic reviews in Korea.